The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jan.15285
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in women with breast and gynaecologic cancers: A systematic review

Abstract: Aim:The current study aimed to systematically review the data obtained from studies on women with breast and gynaecologic cancers subjected to Intimate Partner Violence (IPV).Design: Systematic review without meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
(261 reference statements)
0
3
0
Order By: Relevance
“…Using data from the Pregnancy Risk Assessment Monitoring System (United States), in a cross‐sectional sample of 43,837 individuals with a live birth, respondents with disabilities had 2.6 times the odds of experiencing IPV before pregnancy and 2.5 times the odds of experiencing IPV during pregnancy, compared to individuals in the perinatal period without disabilities (Alhusen et al, 2023). In a systematic review to examine the relationship between IPV exposure and women with breast and gynaecologic cancers, Sheikhnezhad et al (2023) highlight that women with these types of cancer are at the greatest risk of psychological IPV and that maintaining a relationship with the perpetrator negatively influenced their use and access to treatment and quality of life during treatment.…”
Section: Provision Of Person‐centred and Trauma‐and Violence‐informed...mentioning
confidence: 99%
“…Using data from the Pregnancy Risk Assessment Monitoring System (United States), in a cross‐sectional sample of 43,837 individuals with a live birth, respondents with disabilities had 2.6 times the odds of experiencing IPV before pregnancy and 2.5 times the odds of experiencing IPV during pregnancy, compared to individuals in the perinatal period without disabilities (Alhusen et al, 2023). In a systematic review to examine the relationship between IPV exposure and women with breast and gynaecologic cancers, Sheikhnezhad et al (2023) highlight that women with these types of cancer are at the greatest risk of psychological IPV and that maintaining a relationship with the perpetrator negatively influenced their use and access to treatment and quality of life during treatment.…”
Section: Provision Of Person‐centred and Trauma‐and Violence‐informed...mentioning
confidence: 99%
“…These cancers affecting women’s health are a matter of great concern, as they have a significant impact on the lives of those affected [ 2 , 3 ]. A variety of factors make the female population vulnerable to GCs, including genetic predisposition, lifestyle choices, exposure to certain viruses, and hormonal imbalances [ 4 , 5 ]. Numerous studies have demonstrated a correlation between polycystic ovary syndrome (PCOS), a hormonal disorder marked by elevated androgen levels and the presence of numerous ovarian follicles, and endometrial cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Woman may be faced with the physical barrier of being unable to access care by their partners who control many aspects of their life and wellbeing. IPV related barriers to accessing care also include fear of flashbacks, pain, mistrust, or embarrassment associated with male healthcare providers [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%